1994
DOI: 10.1177/095632029400500204
|View full text |Cite
|
Sign up to set email alerts
|

The Antiviral Agent Hypericin hasin vitroActivity against HSV-1 Through Non-Specific Association with Viral and Cellular Membranes

Abstract: The antiviral and virucidal compound, hypericin, was studied regarding its activity and possible mechanism against herpes simplex virus (HSV-1). It was determined that hypericin caused slight inhibition of viral adsorption to and penetration of Vero cells. Additionally, yield reduction assays suggested that hypericin was most effective against HSV-1 as a virucidal agent rather than as an intracellular antiviral agent. Fluorescence microscopy revealed that hypericin initially associated with cytoplasmic membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 23 publications
3
42
0
Order By: Relevance
“…Taken together, these data obtained for Caco-2 cells under serum free conditions suggest that HY is actively taken up after non-specific binding to membrane lipids (38). In addition, alteration of individual steps of endocytosis and membrane cycling changed the intracellular HY location (39), which also indicate the involvement of energy-dependent processes in uptake and distribution of HY in living cells.…”
Section: Discussionmentioning
confidence: 52%
“…Taken together, these data obtained for Caco-2 cells under serum free conditions suggest that HY is actively taken up after non-specific binding to membrane lipids (38). In addition, alteration of individual steps of endocytosis and membrane cycling changed the intracellular HY location (39), which also indicate the involvement of energy-dependent processes in uptake and distribution of HY in living cells.…”
Section: Discussionmentioning
confidence: 52%
“…Hypericin staining of the plasma membrane has also been described [13,17,18]. It was demonstrated that during a short exposure, hypericin was first concentrated in the cell membrane and then penetrated into the cytoplasm [13,17]. However, other reports [14][15][16] did not show specific staining of the plasma membrane.…”
Section: Introductionmentioning
confidence: 88%
“…In spite of a number of investigations of hypericin [12][13][14][15][16][17][18][19], some aspects related to its intracellular distribution remains unclear and contradictory. Thomas and Pardini [12] described red hypericin fluorescence throughout the cytoplasm and plasma membrane in mammary carcinoma cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypericin and pseudohypericin have been reported to inhibit several encapsulated viruses in-vitro, including herpes simplex virus types 1 and 2 (Wood et al 1990 ;Weber et al 1994), and human immunodeficiency virus (HIV)-1 (Meruelo et al 1988 ;Lavie et al 1989 ;Hudson et al 1991 ;LopezBazzocchi et al 1991). Hypericin has also been reported to inactivate murine cytomegalovirus (MCMV) and Sindbis virus .…”
Section: Antiviral Activitymentioning
confidence: 99%